EKSPLORASI THINK PAIR SHARE SEBAGAI MODEL DALAM PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Mutiaramses; Firman, Firman; Desyandri, Desyandri (STKIP Subang, 2021)
The research aims to explore or analyze the effectiveness of implementing the think pair share model in integrated thematic learning in elementary schools. The approach used is qualitative with the type of research that is literature studies. Where researchers analyzed a number of journals and articles from relevant previous research. The data was collected through online traces by searching for journals and articles through google schoolar and j-store. The results of the analysis of various journals found show that the think pair share model is effective in using integrated thematic learning. The effectiveness can be seen from the significant increase in learning outcomes and motivation of students in the two cycles.